Physical activity barriers among adults with physical disabilities or chronic diseases during and after rehabilitation: the ReSpAct cohort study - Wildekamp, Maaike; Krops, A. Leonie; Seves, L. Bregje; Hettinga, J. Florentina; Houdijk, Han; Dekker, Rienk; Hoekstra, Femke (European Journal of Adapted Physical Activity, 2024)
Adults with physical disabilities or chronic diseases face numerous barriers to participate in physical activity (PA). There is little knowledge about how these PA barriers evolve during and after rehabilitation, and how this relates to PA behaviour. In this study, we investigated how perceived PA barriers change over time for adults with physical disabilities or chronic diseases during and after rehabilitation, and their associations with PA behaviour. A total of 1,065 individuals from the longitudinal cohort study Rehabilitation, Sports, and Active Lifestyle (ReSpAct) were examined at various time points from baseline to 52 weeks post-rehabilitation. All participants received counselling as part of a PA promotion program in Dutch rehabilitation care. Longitudinal mixed model analyses showed that the frequency of perceived PA barriers decreased significantly during the transition from rehabilitation to community-based PA. These barriers, categorized as capability, opportunity, and motivation, were also found to be longitudinally negatively associated with self-reported total PA minutes per week. This study provides new insights into the dynamic nature of PA barriers for this diverse population and demonstrates how various types of PA barriers are related to PA behaviour. These findings offer valuable considerations for optimizing PA promotion strategies during and after rehabilitation.
Keywords: behaviour change; health promotion; longitudinal mixed model analyses